Evolução urbana e qualidade de vida: o caso da Avenida Epitácio Pessoa, João Pessoa-PB - Coutinho, Marco Antônio Farias (2004)
This research will be study the Epitácio Pessoa Avenue that serves as main connection between downtown and the beach region of João Pessoa City. This main avenue will reveal us a series of problems that can afect life quality of those who live, work, and transit by the avenue. Trying to understand the urban historical process of João Pessoa City some aspects as the alterations suffered by the landscape of the avenue during eight decades are investigated. The deficiences of a process driven by the real state speculation, without engagement with the identity of this city place and its population will be revealed. The slowness as the urban legislation of the capital occurs is also another factor that instead of adressing to a increasing process, it passes by the resolutins of our daily growth.